Evaluation of knowledge, perception, attitudes, and practices of pain management of children among pediatric nursing personnel of a tertiary care hospital - Patnaik, Sibabratta; Swain, Natabar; Behera, Chinmay Kumar; Jain, Mukesh Kumar; Nayak, Manas Kumar (Indian Journal of Child Health, 2017)
Background: Pain is one of the most misunderstood, under diagnosed and under treated medical problems, particularly in children. If left unaddressed, pain can affect children in ways that will follow them throughout their lives. Nurses play an important role in assessing and managing pain among children during hospitalization. Objective: To evaluate the knowledge, attitude, and practices of pediatric pain management among nursing personnel working in pediatric tertiary care hospital. Materials and Methods: A cross-sectional, self-administered questionnaire-based survey was carried out involving 40 nurses. The questionnaire had 45 items in the domains of personal information, knowledge, and perception toward the pain of pediatric patients, and practices for pain relief. Voluntary participation was ensured and anonymity maintained at all level. Results: The mean age of nurses was 25.53 ± 4.05 years. 90% had a diploma in nursing and 10% were graduates. More than a half (57.5%) of the subjects had experience between 1 and 5 years. The mean score for knowledge was found to be 10.88 ± 2.81 (range 3-16.87%). Most of the participants (87%) thought that children have good pain sensitivity. Only 40% nurses knew about pain scoring system; however, none used pain scoring system in daily practice. None of the nurses were able to answer about the route of administration of morphine for chronic and prolonged pain. Only 44% had shown the correct attitude toward pain in children and 60% participants gave a satisfactory answer regarding practices. Conclusion: Study revealed a deficiency in the knowledge of nurses and their practices regarding pain in children.